Design of a medium scaled air vehicle flapping type / Abbas Siddiqui Mohammed - Abbas Siddiqui, Mohammed (2018)
Flapping wing air vehicle is an ongoing research to master the natural flyers by many different means. Both birds and insects have different methods of producing lift and thrust for hovering and forward flight. Most birds however cannot hover. FWAV is based on avian flight is called ‘ornithopter’ and that is based on insect flight is ‘Entomopter’. Insects have great maneuverability, hovering capabilities and their performance. The purpose of this project is to develop and test the capabilities of flapping wing mechanism that can later be adapter to a biomimetic micro air vehicle (BMAV). In this project ornithopter is used. A mechanical based mechanism is designed for the flapping motion. Preliminary analysis has been done on the wings. The aerodynamic performance characteristics is done based on the numerical analysis. The model was designed in solid works. The mechanism uses gear and carbon fiber rods and to drive the flapping wing and the tail. The complete wing span is used in building the project is about 300 mm. Analysis is done based on ANSYS analysis.